Enhancing Thermal and Mechanical Properties of Ramie Fiber via Impregnation by Lignin-Based Polyurethane Resin - Sucia Okta Handika (MDPI AG, 2021)
In this study, lignin isolated and fractionated from black liquor was used as a pre-polymer to prepare bio-polyurethane (Bio-PU) resin, and the resin was impregnated into ramie fiber (Boehmeria nivea (L.) Gaudich) to improve its thermal and mechanical properties. The isolated lignin was fractionated by one-step fractionation using two different solvents, i.e., methanol (MeOH) and acetone (Ac). Each fractionated lignin was dissolved in NaOH and then reacted with a polymeric 4,4-methane diphenyl diisocyanate (pMDI) polymer at an NCO/OH mole ratio of 0.3. The resulting Bio-PU was then used in the impregnation of ramie fiber. The characterization of lignin, Bio-PU, and ramie fiber was carried out using several techniques, i.e., Fourier-transform infrared spectroscopy (FTIR), differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), pyrolysis-gas-chromatography-mass-spectroscopy (Py-GCMS), Micro Confocal Raman spectroscopy, and an evaluation of fiber mechanical properties (modulus of elasticity and tensile strength). Impregnation of Bio-PU into ramie fiber resulted in weight gain ranging from 6% to 15%, and the values increased when extending the impregnation time. The reaction between the NCO group on Bio-PU and the OH group on ramie fiber forms a C=O group of urethane as confirmed by FTIR and Micro Confocal Raman spectroscopies at a wavenumber of 1600 cm−1. Based on the TGA analysis, ramie fiber with lignin-based Bio-PU had better thermal properties than ramie fiber before impregnation with a greater weight residue of 21.7%. The mechanical properties of ramie fiber also increased after impregnation with lignin-based Bio-PU, resulting in a modulus of elasticity of 31 GPa for ramie-L-isolated and a tensile strength of 577 MPa for ramie-L-Ac. The enhanced thermal and mechanical properties of impregnated ramie fiber with lignin-based Bio-PU resins could increase the added value of ramie fiber and enhance its more comprehensive industrial application as a functional material.